2006
DOI: 10.1074/jbc.m509873200
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Transportation of Diacylglycerol Kinase γ and Its Possible Function in the Nucleus

Abstract: Diacylglycerol kinases (DGKs) convert diacylglycerol (DG) to phosphatidic acid, and both lipids are known to play important roles in lipid signal transduction. Thereby, DGKs are considered to be a one of the key players in lipid signaling, but its physiological function remains to be solved. In an effort to investigate one of nine subtypes, we found that DGK␥ came to be localized in the nucleus with time in all cell lines tested while seen only in the cytoplasm at the early stage of culture, indicating that DG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…Many studies have demonstrated roles for nuclear DGK activity in varied cellular processes. For example, DGK-is activated by nerve growth factor in PC12 cells (101) and thrombin in IIC9 fibroblasts (8,107), DGK-promotes myogenesis in C2C12 cells (23), and DGK-␥ plays a role in regulating the cell cycle in CHO-K cells (72). Interestingly, both DGK-(102) and DGK-(23) are localized in the speckle domains of the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have demonstrated roles for nuclear DGK activity in varied cellular processes. For example, DGK-is activated by nerve growth factor in PC12 cells (101) and thrombin in IIC9 fibroblasts (8,107), DGK-promotes myogenesis in C2C12 cells (23), and DGK-␥ plays a role in regulating the cell cycle in CHO-K cells (72). Interestingly, both DGK-(102) and DGK-(23) are localized in the speckle domains of the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorylation at this site may inhibit the nuclear localization signal function of the C1 domain because Tyr-218 is in the C1 domain, because we previously reported that the C1 domain of DGK␥ has an important role in nuclear transport (17). Binding to importin-␣, a carrier protein that transports some proteins to the nucleus (33)(34)(35), or to an as yet unidentified carrier protein may be regulated by this phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…DGK isoforms have been implicated in various other cellular processes including inhibition of Rap1 signaling ( 9 ) and retinoblastoma-mediated cell cycle control ( 10 ). DGK is activated by nerve growth factor in PC12 cells ( 11 ) and thrombin in IIC9 fi broblasts ( 12,13 ), whereas DGK promotes myogenesis in C2C12 cells ( 14 ) and DGK ␥ plays a role in regulating the cell cycle in CHO-K cells ( 15 ).…”
mentioning
confidence: 99%